Penggunaan Majas Hiperbola pada Iklan Produk Milna Makanan Bayi di Televisi - Saniya Gusti Mahdiya; Rosmilan Pulungan (Education & Learning, 2023)
This study aims to describe and analyze terms of word prominence and the meaning of hyperbole in the advertisement of Milna baby food products on television. This study used a qualitative approach with descriptive data analysis. The source of data in this study was obtained from advertisements for Milna baby food products on television. The data collection of this research used the listening method, recording technique and documenting it. The data analysis technique used was grouping the data, identified, described, and analyzed one by one to get the desired results and draw conclusions from the data. The aspect of highlighting the hyperbole figure of speech found in the advertisement for Milna baby food products on television, includes the aspect of highlighting the word on: a) the advantages of using it, b) indirectly comparing it with other brands. The meaning of hyperbole in the advertisement for Milna baby food products on television emphasizes more on the ingredients, quality and benefits of the product.